Investigating the Relationship between Entrepreneurial Knowledge and Entrepreneurial Interest: A Survey on E-Commerce Entrepreneur - Nizar Alam Hamdani; Intan Sari (Research Collaboration Community (RCC), 2023)
This study is conducted because of the problems in digital economy particularly in the use of e-commerce which currently develops. The phenomenon of e-commerce appearance has radically switched the business landscape. The start-up companies capture new opportunities through innovative business models. Several e-commerce websites are available for general purposes, and the number of websites is increasing from over the time. Realizing the user’s needs are the basic principle in designing the successful websites. This study is intended to find out the relationship between entrepreneurial knowledge and entrepreneurial interest for e-commerce actors in Indonesia. The research method used was quantitative method and the data was analyzed using simple linear regression. The correlation was used by taking comparative approach in which the research method was intended to determine cause-effect relationship. This follows the effect of observing and investigating causal factors through data collection, and the data was processed using SPSS application version 25. To answer the problems formulated in this study, the researchers chose 30 entrepreneurs that use e-commerce. This study showed that there was significant relationship between entrepreneurial knowledge and entrepreneurial interest. This study is the development in form of applied theory. The result of this study explained to what extent entrepreneurs’ attitude and behavior in exploiting information and technology in form of e-commerce. Therefore, it could be discovered the effectiveness and usefulness of e-commerce as selling and purchasing media online. When an entrepreneur acquires the knowledge relating to the usefulness of e-commerce, it will increase the interest of running the business. In addition to, when an entrepreneur understands and comprehends the entrepreneurial knowledge, it will increase the interest to run the business.